2021
DOI: 10.1111/jth.15301
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of carrier status in female members of Japanese hemophilia families

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…This phenomenon has also been observed in some hemophilia A carriers with normal factor VIII levels as in this case and requires further investigation (Tables S1 and S2) [32,[37][38][39]. Shinozawa et al (2021) mention the impact of age and blood group on FVIII:C level [4]. Biguzzi et al (2021) reported that VWF:Ag and FVIII:C increase with age [40].…”
Section: Genetic Analysis Of F8 Genesupporting
confidence: 61%
See 2 more Smart Citations
“…This phenomenon has also been observed in some hemophilia A carriers with normal factor VIII levels as in this case and requires further investigation (Tables S1 and S2) [32,[37][38][39]. Shinozawa et al (2021) mention the impact of age and blood group on FVIII:C level [4]. Biguzzi et al (2021) reported that VWF:Ag and FVIII:C increase with age [40].…”
Section: Genetic Analysis Of F8 Genesupporting
confidence: 61%
“…Despite the clear advantage of nextgeneration sequencing in various settings, Sanger sequencing remains a better option for genetic testing and diagnosis of hemophilia carriers. There may still be a variety of unknown mutations of F8 and F9 target genes as our research and Shinozawa et al (2021) reported [4]. Any new variation found by NGS must still be validated by Sanger sequencing.…”
Section: Genetic Analysis Of F8 Genementioning
confidence: 63%
See 1 more Smart Citation
“…We investigated plasma FIX activity and antigen levels in related female carriers 56 , 57 ( n = 3) of the p.R226W variant (Figure 3 ), to explore its potential influence on the proportion of the WT FIX and the inactive FIX variant circulating in plasma. The mean FIXag levels were higher (153.4 ± 18.6%) than the mean FIX activity (78.0 ± 30.3%), which resulted in an activity/antigen ratio decreased to half (0.50 ± 0.15, Figure 3 ), suggesting similarly increased amounts of both FIX molecules.…”
Section: Resultsmentioning
confidence: 99%
“…The gold-standard for diagnosing HB carrier status remains genetic testing. 18 Genetic testing, however, is reserved for individuals with a high suspicion of HB carriership based on family history, aPTT and/or FIX:C levels. How then can HB carriers be identified?…”
Section: Introductionmentioning
confidence: 99%